Organización Contable en la Farmacia “Pichincha Principal” de la ciudad de Loja, periodo del 01 de julio al 31 de diciembre de 2019. - Erazo Domínguez, Tatiana Katherine (2020)
The development of this thesis work, called ACCOUNTING ORGANIZATION IN THE PHARMACY "PICHINCHA PRINCIPAL" OF THE CITY OF LOJA, PERIOD FROM JULY 1 TO DECEMBER 31, 2019, was developed with the purpose of organizing an accounting process in order to know the development of the company which is dedicated to the purchase and sale of pharmaceutical products, in order for the owner to know the economic - financial situation in a period analyzed, it was carried out according to the proposed objectives, which helped develop the accounting process to get to obtain the financial statements and with the results facilitate decision-making suitable for the growth of the company. In the present thesis work, the Multiple Account System was used that the detailed control of merchandise inventories and to obtain the gross profit in sales, recognize the advantages of the company so that a correct decision-making can be made when wanting to expand its market, for this it was necessary to apply an adequate accounting organization that allows the owner to know the results obtained to achieve the proposed goals. In order to organize the accounting in the Pharmacy "Pichincha Principal", the transaction registry was carried out based on the source documentation provided by the company, beginning with the preparation of the initial inventory, obtaining a record of assets, values and obligations that the company has. company, subsequently, according to the first objective set, an account plan and manual was prepared in accordance with the needs of the “Pichincha Principal” Pharmacy, in the second objective, the design of auxiliary purchases, sales, accounts payable and accounts receivable, payment roles and provisions that facilitated the proper recording of transactions, in the third objective the accounting process was developed, obtaining the financial statements as results, finally in the fourth objective, the application of financial indicators with their respective Interpretation 5 of results, which will result in measuring the liquidity, indebtedness, profitability and performance of the to the company. At the end of the accounting process in the "Pichincha Principal" Pharmacy, and based on the commercial documents, starting with the initial inventory and ending with the financial statements, a profit of $ 8.945,25 was determined, the capital of $ 69.706.50, the total assets of $ 115.632,25 and its total liabilities $ 36.980,50, which indicates that the company has solvency to cover its obligations. After the accounting process, the conclusions and recommendations were made, which constitute a contribution to the Pichincha Principal Pharmacy, which aims to contribute to the development and progress of the company, for this reason it helps the owner to better control the merchandise and thus improve the control of resources, therefore, it helps to obtain better decisions for the company and its financial progress